Computed tomography based estimates of regional gas and tissue volume of the lung in supine subjects with chronic airflow limitation or fibrosing alveolitis. - Millar, A B (1986)
Twelve patients with chronic airflow limitation and 12 patients with a histological diagnosis of fibrosing alveolitis were studied. The calculated mean (SD) tissue volume of a single lung at total lung capacity was 467 (91) ml in the patients with alveolitis, which was 43% (14%) more than predicted for healthy people of the same age, sex, and height. The tissue volume of a single lung at total lung capacity was 436 (82) ml in the patients with chronic airflow limitation, which was 26% (21%) more than predicted. At residual volumes the tissue contents of the fibrotic and the obstructed lungs changed very little (to 407 (84) ml and 433 (84) ml respectively). This allowed tissue volume to be used as a marker of position within the lung, to match inspiratory and expiratory slices and to calculate regional ventilation. In both groups local ventilation was diminished and more variable than in healthy lungs--that is, in the mid 70% of lung volume the local residual volume to total gas volume ratios (RV/TGV) were 32% (10%) in the fibrotic group and 66% (14%) in the group with chronic airflow limitation, compared with 23% (5%) in healthy subjects. As expected, the fibrotic lungs were much denser (0.246 (0.036) g/ml) and the lungs with chronic airflow obstruction were less dense (0.114 (0.026) g/ml) than were healthy lungs (0.126 (0.017) g/ml).